Adjustment of Maintenance Approach for Improved Operability and Safety of Ship Navigation - Bukša, Ante; Šegulja, Ivica; Tomas, Vinko (Promet - Traffic&Transportation, 2012)
By adjusting the maintenance approach towards the significant components of ship’s engines and equipment, through the use of operational data from the ship machinery’s daily reports, higher operability and navigation safety can be achieved. The proposed maintenance adjustment model consists of an operation data analysis and risk analysis. The risk analysis comprises the definition of the upper and the lower risk criterion, as well as the definition of a risk index. If the risk index is higher than the lower risk criterion, the component is significant, while it is not significant and has an acceptable risk index if the risk index is lower than the lower risk criterion. For each significant component with a risk index found to be “unacceptable” or “undesirable”, an efficient maintenance policy needs to be adopted. The assessment of the proposed model is based on data regarding the power engine original operation throughout a 13-year period. The results of engine failure examinations reveal that the exhaust valve is the most vulnerable component with the highest rate of failure. For this reason the proposed model of adjusting the maintenance approach has been tested on the exhaust valve sample. It is suggested that the efforts to achieve higher ship operability and navigation safety should go in the direction of periodical adjustments of the maintenance approach i.e. choosing an efficient maintenance policy by reducing the risk indices of the significant engine components.KEY WORDS: maintenance adjustment approach, risk analysis, risk index, lower risk criterion, upper risk criterion, significant components, ship navigation